Medical management of benign prostatic hyperplasia: Results from a population-based study - Bishr, Mohamed; Boehm, Katharina; Trudeau, Vincent; Tian, Zhe; Dell’Oglio, Paolo; Schiffmann, Jonas; Jeldres, Claudio; Sun, Maxine; Shariat, Sharokh F.; Graefen, Markus; Saad, Fred; Karakiewicz, Pierre I. (Canadian Urological Association Journal, 2016)
Introduction: In men with bothersome lower urinary tract symptoms (LUTS), medical treatment usually represents the first line. We examined the patterns of medical management of benign prostatic hyperplasia (BPH) in the Montreal metropolitan area, within the context of a case control study focusing on incident prostate cancer. Methods: Cases were 1933 men with incident prostate cancer. Population controls included 1994 age-matched men. In-person interviews collected sociodemographic characteristics and medical history, including BPH diagnosis, its duration, and type of medical treatment received. Baseline characteristics were compared by the chi-square likelihood test for categorical variables and by the students t-test for continuously coded variables. Results: Overall, 1120 participants had history of BPH, of those 53.7% received medical treatment for BPH. Individuals with medically treated BPH, compared to individuals with medically untreated BPH, were older at index date [mean: 66.9 vs. 64.9 years, p˂0.001] and at diagnosis of BPH [mean: 62.3 vs. 60.3 years, p˂0.001]. They also had a longer duration of BPH-history [mean: 4.7 vs. 4.0 years, p=0.02]. Regarding medical treatment, monotherapy was more often used than combination therapy [87.6% vs. 12.4%, p˂0.001]. Alpha-blockers (69.9%) were most commonly used as monotherapy, followed by 5alpha-reductase inhibitors (5ARIs) (26.6%). Alpha-blockers plus 5ARIs were the most common combination therapy (97.3%). Conclusions: Despite evidence from randomized, controlled trials for better efficacy with use of combination therapy, monotherapy consisting of alpha-blockers or 5ARI, in that order, is most frequently used. Additionally, 5ARI use was more common than previously reported (27% vs. 15%).